Paradoxes of gender - Lorber, Judith (Yale University Press, 1994)
Annotation In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: Sex role.; Gender identity.; Social institutions.; Feminist theory.; Social institutions; Gender Identity; Gender Role; Rôle selon le sexe.; Identité de genre.; Institutions sociales.; Théorie féministe.; sex role.; social institutions.; SOCIAL SCIENCE -- Gender Studies.; HISTORY -- General.; Feminist theory; Gender identity; Sex role; Sekseverschillen.; Theorieën.; Relações de gênero (desenvolvimento social; aspectos culturais); Interação interpessoal.; Identité sexuelle.; Feminism.